2015
DOI: 10.18030/socio.hu.2015en.128
|View full text |Cite
|
Sign up to set email alerts
|

Discourses about the meaning of the local food Investigations in Romanian urban contexts

Abstract: Up to now only a few studies about local food consumption in Romania have been realized and the majority of them are quantitative investigations. The aim of the present research which is based on focus group interviews was to bring further nuance to these previous quantitative data by asking the respondents to develop deeper narratives about what local food means to them, how they relate to local foods, how they perceive the different features of local foods (e.g. tradition, organic, taste, ingredients, etc.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
3
0
2
Order By: Relevance
“…The results of the current investigation regarding the existence of different attitudes between heterogeneous cultural groups in South Tyrol, confirms that local food is a culturally driven complex phenomenon (Nistor 2015, Martinez et al 2010, Pratt 2007. More specifically, the cultural background influences the meaning of local food associated by individual consumers.…”
Section: Cultural Background and Local Foodsupporting
confidence: 76%
See 1 more Smart Citation
“…The results of the current investigation regarding the existence of different attitudes between heterogeneous cultural groups in South Tyrol, confirms that local food is a culturally driven complex phenomenon (Nistor 2015, Martinez et al 2010, Pratt 2007. More specifically, the cultural background influences the meaning of local food associated by individual consumers.…”
Section: Cultural Background and Local Foodsupporting
confidence: 76%
“…Living together in the region the German and Italian language groups cultivate their own culture (BLS 2015), and this aspect has an influence on food choice, values and attitudes towards local food. Therefore, our research hypothesis is that differences exist across heterogeneous cultural groups, since food consumption itself indicates already that 'people are able to make visible and communicate the social and cultural differences between them and that they adhere to certain values and ideologies' (Nistor 2015: 129, Dolan 2002. We base this hypothesis on the evidence reported in previous cross-cultural studies showing that sociocultural aspects determine consumers' feelings and needs, resulting in differences in food-related aspects even in relatively homogeneous countries (Guerrero et al 2009: 346).…”
Section: Introductionmentioning
confidence: 99%
“…Reconsidering the access and affording adequate amounts and qualities of food would also bring a decrease in phenomena such as malnutrition, lack of healthy food, and starvation (Rosegrant -Cline 2003:1917. Sociological research focused mainly on Eastern European countries and rural areas and consumer groups has shown that organic farming and food production is a little-known, novel phenomenon that takes local economic structures into account in different ways and measures (Bilewitz -Śpiewak 2016:147; Kónya 2016:3-5; Laki 2016:8;Nistor 2015). Organic farming in Hungary has lost some of its significance sin ce 2004 as it does not get any significant consideration in state aid policies.…”
Section: Social Science Interests In Nutritionmentioning
confidence: 99%
“…Így van, akinek a nagyszülők kertjéből származó zöldség számít helyinek, van pedig, akinek egy székelyföldiként aposztrofált termék. (Nistor, 2015). Éppen ezért sokkal hasznosabb lehet a helyi termékeket fogyasztó közönséget attitűdjeik, értékítéleteik, illetve fogyasztói viselkedési mintáik mentén megkülönböztetni, mint társadalmi-demográfiai jellemzőik alapján, ahogy erre Tregear (2007) is rávilágít a helyi termékeknek a vidékfejlesztésben játszott szerepét a piaci folyamatokon és fogyasztói szokásokon, viselkedéseken keresztül vizsgáló írásában.…”
Section: A Helyi Gazdaságfejlesztés éS a Helyi Termék Elméleti-fogalmunclassified
“…A helyi termék meghatározásának a szakirodalom szerint is egyik legfontosabb kritériuma, hogy az földrajzi helyhez (földrajzilag meghatározható térhez) köthető legyen, ám a különböző szakterületek eltérő nézőponton vannak a lokalitás lehetséges határainak meghatározását, kijelölését illetően (Mezei, 2006b). A helyi élelmiszerekkel kapcsolatban pedig korábban éppen arra hívtuk fel a figyelmet, hogy nemcsak a kutatók, de a potenciális fogyasztók is meglehetősen eltérően értelmezik egy élelmiszertermék lokalitását (Nistor, 2015). A csíki sör elnevezés -ahogyan azt a korábbi fejezetekben tárgyaltuk -a Csíki-medencében, Csíkszereda környékén élő székelység számára a mindenkori Csíkszeredában gyártott sört jelentette.…”
Section: Igazi Csíki Sör -Valódi Helyi Termék?unclassified